Association of Thyroid Stimulating Hormone with Insulin Resistance in Women with Polycystic Ovarian Syndrome - Naher, Salma; Begum, Sultana Rajia; Ali, Liaquat; Hakim, Maksumul (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Polycystic Ovarian Syndrome (PCOS) is a major cause of female infertility which is thought to be associated with Insulin Resistance (IR). However the nature and degree of IR have been shown to vary in different populations. PCOS women have also been reported to have increased prevalence of subclinical hypothyroidism which has been postulated to be determinants of IR. The natures of thyroid involvement have also been shown to vary between populations. Objectives: The study was undertaken to explore the distribution of IR and thyroid dysfunction as assessed by Thyroid Stimulating Hormone (TSH) levels among PCOS subjects and also to investigate the association of IR with TSH in women with PCOS. Materials and Methods: One hundred and fifty one PCOS patients (age in years 24±5; M±SD) were studied. PCOS was diagnosed by Rotterdam criteria. Fasting serum C-peptide was measured by Enzyme Linked Immuno Sorbide Essay (ELISA) and serum TSH was measured by Microparticle Enzyme Immunoassay (MEIA). Serum glucose was estimated by Glucose-Oxidase method (GOD-PAP). Insulin sensitivity was assessed by using Homeostasis Model Assessment (HOMA). Results: The mean serum C-peptide (nmol/l) and HOMA%S were 0.67 (±0.35) and 85 (±42) respectively. The median (Range) serum TSH level (?lU/ml) of the study subjects was found to be 2.49 (0.66 to 20.86). Insulin sensitivity was found to be 26%, 47%, 17% and 10% in those who had HOMA%S level at the range of <50, 50-100, 101-150 and >150 respectively. Of the total PCOS subjects, 85% had normal level of TSH value whereas only 15% PCOS subjects had subclinical hypothyroidism. The median serum TSH level of the insulin resistance and non-resistance groups were 2.25 (0.89-5.71) and 2.58 (0.74-20.86) respectively. On Pearson's correlation analysis insulin sensitivity was not found to be any significant association with TSH in the PCOS subjects. Conclusion: The study revealed that there was no significant association with IR and TSH in the PCOS subjects. Journal of Armed Forces Medical College Bangladesh Vol.11(1) 2015: 69-73